Persepsi Siswa Tentang Pelayanan Tenaga Administrasi Sekolah di SMKN 1 Enam Lingkung - Pungki Cindy Ashari; Hadiyanto Hadiyanto; Nelitawati Nelitawati; Ermita Ermita (Universitas Negeri Padang, 2022)
This study aims to obtain an overview of students' perception of school administration services. This research is descriptive quantitative. The population of this study is students of grade X and grade XI in SMKN 1 Enam Lingkung. The results showed that students' perception of school administration services in SMKN 1 Enam Lingkung: a) seen from the hospitality aspect was in a high category with an average score of 4.16, 2) judging from the comfort aspect is in the high category with an average score of 4.13, 3) judging from the aspect of responsibility is in the high category with an average score of 4.11, d) seen from the aspect of response is in the high category with an average score of 4.15 , 5) seen from the aspect of ease in obtaining service is in the high category with an average score of 4.20. Thus, it can be concluded that students' perception of school administration services in SMKN 1 Enam Lingkung is in a high category with an average score of 4.15. The advice that can be given is an effort to maintain and improve the services of school administration personnel for the better